Electrical energy from compressor’s air conditioning / Muhammad Khalaf Ab Aziz, Mohammad Affendy Ibrahim & Nik Muhammad Akman Nik Zaudin - Ab Aziz, Muhammad Khalaf; Ibrahim, Mohammad Affendy; Nik Zaudin, Nik Muhammad Akman (Faculty of Electrical Engineering, 2014)
Due to wasteful wind energy from air compressor’s air conditional, this project is about to change wind energy that can produce electrical energy that can use in daily life. Electrical energy from air compressor’s air conditioning can acts as mini generator that basically using wind energy to generate an electrical energy. By using 12v DC motor, this project can charge the battery because it output is 12v and in Direct Current condition. Thus, this project can convert it from Direct current (DC) to Alternating current (AC) energy by using circuit converter. This project needs four 12v DC motors in series connection to produce 12V. After changing the current, this converter circuit is connected to the step-up transformer from 12V to get output 240V/AC. In this project, electrical energy generated from the mini wind turbine, then connected to the lamp and built a lamp as a mini theme park. Not like the generator in the market, this generator does not produce a pollution such as noise and air pollution.